Five-Dimensional Cosmological Model with One Dimensional Cosmic String Coupled with Zero Mass Scalar Field in Lyra Manifold - Mete, V. G.; Deshmukh, V. (Journal of Scientific Research, 2023)
A five-dimensional Bianchi type-III string cosmological model is studied with a one-dimensional cosmic string in the presence of zero mass scalar field in the context of the Lyra manifold. Exact solutions of Einstein's field equations are obtained by assuming quadratic equation of state (EoS) of the form p = kρ2 + ρ, where k is a constant and strictly k > 0 . The physical and geometrical aspects of the investigated model are analyzed in detail.